Effects of 14-week strength training period on passive movement evoked fields, stretch reflex functioning, muscle strength and balance - Seipäjärvi, Santtu (2018)
Strength training is known to affect the nervous system in various ways most often leading to improvements in performance. Changes occurring due to training or aging can provide us more information about the nervous system controlling our movements. Reflexes are an essential part of our body’s “toolbox” in movement control and force production. One of particular interest is the functioning of the stretch reflex that is highlighted in some of the motor control theories aswell. Stretch reflex is widely known muscle response to stretch but the question whether a transcortical loop exists and affects the muscle response is still under debate.